(untitled) (Bioscience Journal, 2020)
The value of coffee presents a significant increase influenced by the improvement of the beans quality, so that a coffee made by beans with an inferior quality has a lower acceptance in the market and a reduction in therms of commercialization value. The different time of fermentation of the coffee in water can give rise to different beverage and physiological quality of its seeds, and may interfere in its commercialization value and in the production of seedlings in nurseries. The target of this study was to identify the best time of fermentation of the beans and seeds of Arabic coffee in the region of Mutum-MG, aiming to obtain a better quality of the drink and a better physiological quality of the seeds. The experimental design was completely randomized with seven treatments, 0, 6, 12, 18, 24, 30 and 36 hours of fermentation in water. Four replicates per treatment were used. Each repetition consisted in ten liters of coffee. The samples were submitted to a drying process in covered suspended terrarium until reaching 12% moisture. The evaluations consisted in the realization of these sensorial analysis (AS); % water content (%U); electrical conductivity (EC); first germination count (FCG); percentage of germination (%G); total fresh mass (TFM); total dry mass (TDM) and radicle length (RL). The 18 hours fermentation time provided a better quality of coffee drink obtaining a score of 84 points and also resulted in a higher physiological quality of the seeds. Excess fermentation impaired the quality of the drink and physiological quality.